Hypertension as one of the risk factors for age-related macular degeneration - Soni Priartso, Soni Priartso (Universitas Gadjah Mada, 2001)
Background: Age-related macular degeneration (ARMD) is one of the causes of loss of central vision in older people. While age is the undisputed, the most important risk factors such as genetic, race, sex, sunlight exposure, diet, vitamin, smoking, cardiovascular disease, hypercholesterolemia, and hypertension have been incriminated to be associated with the development of ARMD. The study of ARMD is very rare in Indonesia.Objectives: To investigate the possible association of presumed hypertension, and other risk factors in patients with age-related macular degeneration.Methode: A case-control study of 120 subjects, 60 cases with ARMD and 60 cases of normal control in Dr. Sardjito General Hospital and Dr. YAP. Eye Hospital, Yogyakarta. ARMD and normal control were compared. Interview, eye examination, blood pressure, and blood sample were performed. Results: Hypertension was observed in 38 (76%) of 60 patients with age-related macular degeneration. Of 60 normal control patients, only 12 (24%) had hypertension. Statistical analysis result showed that hypertension was one of the risk factors for the development of age-related macular degeneration OR: 6,909 (3,037-15,720). But hypertension was not a predictor for the development of age-related macular degeneration (regression coefficient = 0,0000).Conclusion: Besides other risk factors, hypertension is one of the risk factors for the development of age-related macular degeneration.Keywords: age-related macular degeneration - central vision - older people - risk factors - hypertension